Effect of Aspirin Consumption during Pregnancy on Fetal and Placental Weights and Histomorphometric Changes of the Fetal Stomach in Rats - Maryam Heydarzadeh; Mahnaz Azarnia; Seyed Homayoon Sadraie; Gholamreza Kaka; Majid Naghdi (Fasa University of Medical Sciences, 2015)
Background & Objective: Due to the relevant use of aspirin to relieve pain and common symptoms of gastric ulcer and possible malicious effects on fetus, this study investigates the histomorphologic effects of aspirin on the stomach tissue in rat embryos.    Materials & Methods: In this experimental study, 30 pregnant female rats were randomly divided into six groups including control group with no intervention, sham group, and four experimental groups receiving different dosages of 75, 100, 200, and 300 mg/kg aspirin by gavage. Pregnant rats were sacrificed on the 20th day of pregnancy and the fetuses and their placenta were examined from morphologic viewpoint. Fetal stomachs were removed, fixed, processed, and sectioned. Histological sections were stained with hematoxylin - eosin and were measured by histomorphometric methods.    Results: There were no apparent abnormalities in the fetus of all studied groups. Mean fetal and placental weights and the Crown Rump Length (CRL) in experimental group at the dosage of 100 mg /kg increased significantly compared to control and sham groups. Our results showed a significant increase in the average thickness of the submucousal layer in both stratified cornified squamous epithelium and simple columnar epithelium of fetal stomach in the experimental groups receiving 200 and 300 mg/kg aspirin compared to sham and control groups.    Conclusion: No fetal apparent abnormality was seen. However, histologic evaluations revealed that the use of high dosages of aspirin increase the submucousal layer thickness in both the keratinized and glandular epithelium, significantly.